Risk Management in the Manufacturing Production Process: Integration of Automation Technology and Machine Safety - Suhara, Ade; Aulia Nanda, Rizki; Dewadi, Fathan Mubina; Karyadi, Karyadi (YCMM, 2024)
This study explores the integration of automation technology and machine safety in risk management within the manufacturing production process. By employing a combination of qualitative and quantitative methods, including literature reviews, surveys, and data analysis, the research identifies the critical role of automation technologies such as robotics, IoT, and predictive analytics in mitigating risks. These innovations improve operational efficiency, enhance worker safety, and ensure compliance with evolving regulatory standards. Key findings highlight the dual benefits of reducing downtime and preventing workplace accidents, while also emphasizing the necessity of adaptive risk management strategies. The study concludes that aligning advanced technologies with proactive safety protocols fosters a more resilient and productive manufacturing environment.